Brazing method for aluminum nitride ceramic and oxygen-free copper and composite brazing filler metal
By adding niobium powder to the silver-copper-titanium brazing filler metal, the thermal expansion coefficient mismatch between aluminum nitride ceramics and oxygen-free copper is reduced, the joint stress is alleviated, the interface bonding strength between aluminum nitride ceramics and oxygen-free copper is improved, the problem of low interface bonding strength is solved, and higher joint strength and reliability are achieved.
Patent Information
- Application Number
- CN202511200653.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2045-08-26
AI Technical Summary
In the prior art, the brazing of aluminum nitride ceramics and oxygen-free copper has the problem of low interface bonding strength, which is mainly due to the large residual thermal stress caused by the mismatch of thermal expansion coefficients.
Adding niobium powder to the silver-copper-titanium solder can reduce the thermal expansion coefficient of the solder alloy, relieve joint stress, and improve interface bonding strength through the low thermal expansion coefficient and good plastic deformability of niobium particles.
By adding niobium powder, the thermal expansion coefficient mismatch between aluminum nitride ceramics and oxygen-free copper is reduced, the joint stress is relieved, the joint strength and peel strength are improved, and the reliability of the aluminum nitride copper clad laminate is enhanced.
Smart Images

Figure CN120715330A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present disclosure relate to the field of electronic packaging technology, and more particularly, to a brazing method and composite brazing material for aluminum nitride ceramics and oxygen-free copper. Background Art
[0002] As power devices continue to develop, their operating voltages and currents continue to increase, placing more stringent demands on their heat dissipation capabilities. Aluminum nitride ceramics have higher thermal conductivity than alumina ceramics, lower dielectric constant than silicon carbide ceramics, and a thermal expansion coefficient similar to that of chips, offering broad application and development prospects. The preparation processes for aluminum nitride ceramic copper-clad laminates include direct copper plating, direct copper bonding, active metal brazing (AMB), and laser-activated metallization. The active metal brazing process offers advantages such as simplicity, wide applicability, high interface bonding strength, and strong current-carrying capacity.
[0003] Silver-copper-titanium brazing alloy is the most commonly used active brazing alloy system for joining ceramics to metals, and active brazing has been achieved for a variety of ceramic / metal systems. However, the active metal brazing process still has drawbacks due to the large mismatch in the coefficient of thermal expansion (CTE) between ceramics and metals. This leads to the shrinkage and deformation of the materials during cooling, resulting in significant residual thermal stress at the joint interface, which reduces interfacial bonding strength. Summary of the Invention
[0004] The purpose of the present disclosure is to provide a brazing method and composite brazing material for aluminum nitride ceramic and oxygen-free copper, thereby overcoming, at least to a certain extent, the problem of low interface bonding strength caused by the limitations and defects of related technologies.
[0005] According to one aspect of the present disclosure, a method for brazing aluminum nitride ceramics and oxygen-free copper is provided, comprising: placing silver-copper-titanium brazing filler metal and niobium powder into a ball mill and ball-milling them using alcohol as a dispersion medium to obtain a brazing filler metal suspension; drying the brazing filler metal suspension to obtain a composite brazing filler metal; adding ethyl cellulose to a mixed solvent of terpineol and diethylene glycol butyl ether acetate, heating and dissolving the mixture to obtain a mixed solution; sequentially adding hydrogenated castor oil and fatty alcohol polyoxyethylene ether to the mixed solution, heating until dissolved, and obtaining a solder paste binder with uniform composition; stirring the composite brazing filler metal and the solder paste binder to obtain a composite brazing filler metal paste; coating the composite brazing filler metal paste on a bonding area of the aluminum nitride ceramic, and stacking an oxygen-free copper foil on the aluminum nitride ceramic coated with the composite brazing filler metal paste for brazing.
[0006] In an exemplary embodiment of the present disclosure, the composite solder includes silver-copper-titanium solder and niobium powder. The silver-copper-titanium solder contains 68.0-70.5 wt% silver, 4.0-5.0 wt% titanium and copper, and the mass of the niobium powder is 0-10 wt% of the total mass of the composite solder.
[0007] In an exemplary embodiment of the present disclosure, drying the solder suspension to obtain a composite solder includes: placing the solder suspension in a vacuum drying oven and drying it at a target temperature to obtain a dried composite solder; the target temperature is less than or equal to 80°C.
[0008] In an exemplary embodiment of the present disclosure, the particle size of the silver-copper-titanium powder is less than or equal to 45 μm, and the particle size of the niobium powder is less than or equal to 80 nm.
[0009] In an exemplary embodiment of the present disclosure, the solder paste binder includes: 5-15 wt% ethyl cellulose, 15-25 wt% diethylene glycol butyl ether acetate, 1-5 wt% hydrogenated castor oil, 0.1-3 wt% fatty alcohol polyoxyethylene ether and terpineol.
[0010] In an exemplary embodiment of the present disclosure, the mass ratio of the composite solder to the binder for solder paste is 9:1 to 8:2.
[0011] In an exemplary embodiment of the present disclosure, an oxygen-free copper foil is stacked on an aluminum nitride ceramic coated with a composite brazing filler metal for brazing, comprising: placing the oxygen-free copper foil stacked on the aluminum nitride ceramic coated with a composite brazing filler metal into a furnace, heating the furnace to a first temperature at a heating rate under a target vacuum degree and maintaining the temperature for a first time, and heating the furnace to a second temperature and maintaining the temperature for a second time, so as to braze the aluminum nitride ceramic and the oxygen-free copper foil.
[0012] In an exemplary embodiment of the present disclosure, the target vacuum degree is higher than 3×10 ‒3 Pa.
[0013] In an exemplary embodiment of the present disclosure, the heating rate is 3°C / min~10°C / min, the first temperature is 450°C, the first time is 10min~30min, the second temperature is 840°C~920°C, and the second time is 5min~20min.
[0014] According to one aspect of the present disclosure, a composite solder is provided, which is used to perform any of the above-mentioned methods for brazing aluminum nitride ceramics and oxygen-free copper; wherein the composite solder comprises a silver-copper-titanium solder and niobium powder, the silver-copper-titanium solder comprising 68.0-70.5 wt% silver, 4.0-5.0 wt% titanium and copper, and the mass of the niobium powder is 0-10 wt% of the total mass of the composite solder.
[0015] In the technical solutions provided in the embodiments of the present disclosure, on the one hand, niobium powder is added to a silver-copper-titanium brazing filler metal to prepare a composite brazing filler metal. Niobium particles are used to enhance the strength of the silver-copper-titanium composite brazing filler metal in connecting aluminum nitride ceramics to oxygen-free copper. By adding niobium particles to the silver-copper-titanium brazing filler metal, the thermal expansion coefficient of niobium is reduced by taking advantage of the fact that the thermal expansion coefficient of niobium is much lower than that of the silver-copper-titanium brazing filler metal, thereby reducing the thermal expansion coefficient mismatch between the aluminum nitride ceramics and oxygen-free copper. This alleviates the residual stress in the joint between the aluminum nitride ceramics and oxygen-free copper in the related art, improves the joint strength between the aluminum nitride ceramics and oxygen-free copper foil, and increases the peel strength. On the other hand, niobium has good ductility. During the load-bearing process, niobium particles can undergo a certain degree of plastic deformation to absorb some energy, alleviating stress concentration within the silver-copper-titanium composite brazing filler metal layer and improving the reliability and quality of the aluminum nitride copper-clad laminate.
[0016] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings are incorporated into and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and those skilled in the art can derive other drawings based on these drawings without inventive effort.
[0018] Figure 1 A flow chart schematically illustrates a method for brazing aluminum nitride ceramic and oxygen-free copper in an embodiment of the present disclosure.
[0019] Figure 2 The microstructure morphology of the aluminum nitride ceramic copper-clad laminate joint prepared according to Example 1 is schematically shown. DETAILED DESCRIPTION
[0020] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that the present disclosure will be more comprehensive and complete and will fully convey the concepts of the example embodiments to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or that other methods, components, devices, steps, etc. may be employed. In other cases, well-known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.
[0021] The terms "a", "an", "the" and "said" are used in this specification to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express open-ended inclusion and mean that additional elements / components, etc. may exist in addition to the listed elements / components, etc.; the terms "first" and "second" are used only as labels and are not intended to limit the quantity of their objects.
[0022] Silver-copper-titanium brazing alloy is the most commonly used active brazing alloy system for joining ceramics to metals, and active brazing has been achieved for a variety of ceramic / metal systems. However, the active metal brazing process still suffers from the significant mismatch between the coefficient of thermal expansion (CTE) of the ceramic and metal. This leads to shrinkage and deformation of the materials during cooling, resulting in significant residual thermal stress at the joint interface, which in turn reduces interfacial bonding strength. Therefore, alleviating residual stress in the weld joint is key to fabricating high-reliability aluminum copper nitride laminates.
[0023] To address the aforementioned issues, the presently disclosed embodiments provide a method for brazing aluminum nitride ceramics and oxygen-free copper, as well as a composite brazing filler metal for brazing aluminum nitride ceramics and oxygen-free copper. This composite brazing filler metal is prepared by adding niobium powder to a conventional silver-copper-titanium brazing filler metal. The addition of niobium particles reduces the thermal expansion coefficient of the brazing filler metal and allows the niobium particles to undergo a certain degree of plastic deformation during load-bearing, absorbing some of the energy. This solves the problem of high residual stress and low joint strength in aluminum nitride ceramic and oxygen-free copper joints.
[0024] refer to Figure 1 As shown in , the brazing method of aluminum nitride ceramic and oxygen-free copper mainly includes the following steps: In step S110, silver-copper-titanium solder and niobium powder are placed in a ball mill and ball milled using alcohol as a dispersion medium to obtain a solder suspension; In step S120, the solder suspension is dried to obtain a composite solder; In step S130, ethyl cellulose is added to a mixed solvent of terpineol and diethylene glycol butyl ether acetate and heated to dissolve to obtain a mixed solution. Hydrogenated castor oil and fatty alcohol polyoxyethylene ether are sequentially added to the mixed solution and heated until dissolved to obtain a solder paste binder having uniform composition. In step S140, the composite solder and the solder paste binder are stirred to obtain a composite solder paste; In step S150, a composite solder paste is coated on the bonding area of the aluminum nitride ceramic, and an oxygen-free copper foil is stacked on the aluminum nitride ceramic coated with the composite solder paste for brazing.
[0025] Next, the brazing method of aluminum nitride ceramic and oxygen-free copper in the embodiment of the present disclosure is described in detail.
[0026] In step S110, silver-copper-titanium solder and niobium powder are placed in a ball mill and ball milled using alcohol as a dispersion medium to obtain a solder suspension.
[0027] In the disclosed embodiment, the silver-copper-titanium solder is an active solder system for connecting ceramics to metals. The silver-copper-titanium solder contains 68.0-70.5 wt% silver, 4.0-5.0 wt% titanium and copper. Specifically, the mass of silver accounts for 68.0%-70.5% of the total mass of the silver-copper-titanium solder. The mass of titanium accounts for 4.0%-5.0% of the total mass of the silver-copper-titanium solder, and the remaining component in the silver-copper-titanium solder is copper. The mass of niobium powder is 0-10% of the total mass of the composite solder. The particle size of the silver-copper-titanium powder is less than or equal to 45 μm, and the particle size of the niobium powder is less than or equal to 80 nm.
[0028] Silver-copper-titanium solder and niobium powder can be weighed according to the above ratio, placed in a ball mill, and ball-milled using alcohol as a dispersion medium to obtain a solder suspension.
[0029] In step S120, the solder suspension is dried to obtain a composite solder.
[0030] In the disclosed embodiments, the solder suspension can be placed in a vacuum drying oven and dried at a target temperature to obtain a dried composite solder. The target temperature is less than or equal to 80°C, and can be, for example, 40°C, 50°C, 60°C, 80°C, or other suitable temperatures. The drying time is not limited, as long as the composite solder can be obtained.
[0031] In step S130, ethyl cellulose is added to a mixed solvent of terpineol and diethylene glycol butyl ether acetate and heated to dissolve to obtain a mixed solution. Hydrogenated castor oil and fatty alcohol polyoxyethylene ether are sequentially added to the mixed solution and heated until dissolved to obtain a solder paste binder with uniform composition.
[0032] In the embodiment of the present disclosure, pineol and diethylene glycol butyl ether acetate are mixed to form a mixed solvent, and ethyl cellulose is added to the mixed solvent, and the mixed solvent with the addition of ethyl cellulose is heated and stirred until the ethyl cellulose is completely dissolved to obtain a mixed solution. Among them, pineol is the main solvent, which provides good volatility and wettability. Diethylene glycol butyl ether acetate is an auxiliary solvent, which adjusts the volatilization rate and improves stability. Ethyl cellulose is a thickener, which adjusts the viscosity and enhances adhesion. The mass percentage of ethyl cellulose is 5~15wt%, and the mass percentage of diethylene glycol butyl ether acetate is 15~25wt%. The mixed solvent with the addition of ethyl cellulose can be heated to a first preset temperature, which can be 60~70°C. The heating of the mixed solution can be water bath heating or non-water bath heating, which is determined according to actual needs.
[0033] Furthermore, hydrogenated castor oil and fatty alcohol polyoxyethylene ether are sequentially added to the mixed solution and heated until dissolved to produce a uniform solder paste binder. The hydrogenated castor oil is a thixotropic agent used to thicken and improve wettability, thereby enhancing stability. The fatty alcohol polyoxyethylene ether is a surfactant used to enhance wettability and reduce surface tension.
[0034] The mass percentage of hydrogenated castor oil is 1-5wt%, and the mass percentage of fatty alcohol polyoxyethylene ether is 0.1-3wt%. The mixed solution containing hydrogenated castor oil and fatty alcohol polyoxyethylene ether can be heated to a second preset temperature, which can be higher than the first preset temperature, for example, 85-95°C. The mixed solution containing hydrogenated castor oil and fatty alcohol polyoxyethylene ether can be heated in a water bath or a non-water bath, depending on actual needs. When the hydrogenated castor oil and fatty alcohol polyoxyethylene ether added to the mixed solution are completely dissolved, a uniform solder paste binder can be produced. It should be noted that the composition of the solder paste binder can be determined based on the composition of the additives and the composition of the mixed solvent. For example, the solder paste binder includes 5-15wt% ethyl cellulose, 15-25wt% diethylene glycol butyl ether acetate, 1-5wt% hydrogenated castor oil, 0.1-3wt% fatty alcohol polyoxyethylene ether, and terpineol.
[0035] In step S140 , the composite solder and the solder paste binder are stirred to obtain a composite solder paste.
[0036] In the disclosed embodiments, after preparing the composite solder paste, the composite solder and the solder paste binder may be stirred and mixed according to a mass ratio to obtain the composite solder paste, wherein the mass ratio of the composite solder to the solder paste binder is 9:1 to 8:2.
[0037] In step S150, a composite solder paste is coated on the bonding area of the aluminum nitride ceramic, and an oxygen-free copper foil is stacked on the aluminum nitride ceramic coated with the composite solder paste and brazing is performed.
[0038] In the disclosed embodiments, the bonding area refers to the interface region where the aluminum nitride ceramic is connected to other materials such as metals through a specific process, as well as the local area near this region affected by the bonding process. For example, it can be the physical or chemical bonding interface between the aluminum nitride ceramic and the other material. The size of the bonding area can be determined based on actual needs.
[0039] For aluminum nitride ceramics, the composite solder paste prepared in step S140 can be applied to the bonding area of the aluminum nitride ceramic, and the coating thickness can be determined according to actual needs. Furthermore, an oxygen-free copper foil can be stacked on the aluminum nitride ceramic coated with the composite solder paste and brazed. For example, an oxygen-free copper foil can be stacked on the surface of the aluminum nitride ceramic coated with the composite solder paste, and the oxygen-free copper foil can be fixed to the surface of the aluminum nitride ceramic coated with the composite solder paste in a stacked and bonded manner.
[0040] On this basis, the aluminum nitride ceramics stacked with oxygen-free copper foil are placed in a furnace for brazing. The brazing process parameters are: heating to a first temperature and holding it for a first time at a heating rate under a target vacuum, and then heating to a second temperature and holding it for a second time, so as to braze the aluminum nitride ceramics and oxygen-free copper foil. The target vacuum can be higher than 3×10 ‒ 3 Pa. The heating rate is 3℃ / min~10℃ / min, the first temperature is 450℃, the first time is 10min~30min, the second temperature is 840℃~920℃, and the second time is 5min~20min. For example, the temperature can be higher than 3×10 ‒3 Under the vacuum condition of Pa, the temperature is first raised to 450℃ at a heating rate of 3℃ / min~10℃ / min and kept for 10min~30min to volatilize the organic matter in the composite solder paste, and then the temperature is raised to 840℃~920℃ and kept for 5min~30min to complete the brazing process.
[0041] In the disclosed embodiments, niobium powder is added to prepare a composite brazing filler metal. Niobium particles are then used to reinforce the silver-copper-titanium composite brazing filler metal to connect aluminum nitride ceramics to oxygen-free copper. By adding niobium particles to the silver-copper-titanium brazing filler metal, the thermal expansion coefficient of niobium is significantly lower than that of the silver-copper-titanium brazing filler metal, thereby reducing the thermal expansion coefficient mismatch between the aluminum nitride ceramics and the oxygen-free copper, alleviating joint stress and improving joint strength. Furthermore, niobium exhibits good ductility. During load-bearing, the niobium particles can undergo a certain degree of plastic deformation, absorbing some of the energy and alleviating stress concentration within the brazing filler metal layer.
[0042] Next, the brazing method of aluminum nitride ceramic and oxygen-free copper disclosed in the present invention is described with reference to an embodiment.
[0043] Comparative Example 1 Step 1: Soak the copper substrate in dilute hydrochloric acid for several minutes, place it in anhydrous ethanol for ultrasonic cleaning, and then rinse it with distilled water and dry it to remove impurities on the surface of the copper substrate.
[0044] Step 2: Electroplating the dried copper substrate to form an oxygen-containing copper layer on the bonding surface of the copper substrate. The electroplating solution consists of copper sulfate, lactic acid, and water. The concentration of copper sulfate in the electroplating solution is 0.5 mol / L, and the concentration of lactic acid is 2.5 mol / L. During electroplating, the pH of the electroplating solution is adjusted to 11 using a 5 mol / L sodium hydroxide solution. The electroplating current is a constant current of 3 mA, and the electroplating time is 20 minutes.
[0045] Step 3: The aluminum nitride substrate was cleaned with acetone, water, and ethanol using ultrasonic cleaning in sequence, with each ultrasonic cleaning lasting 10 minutes. After ultrasonic cleaning, the substrate was dried in an oven at 80°C.
[0046] Step 4: Heat the dried aluminum nitride substrate in an air atmosphere to form an aluminum oxide layer on the bonding surface of the aluminum nitride substrate.
[0047] Step 5: stacking the copper substrate and the aluminum nitride substrate so that the oxygen-containing copper layer and the aluminum oxide layer are in direct contact to prepare a pre-finished product.
[0048] Step 6: Place the pre-finished product steadily in a sintering furnace, purge it three times, and evacuate it. Then, keep it warm. After this, allow it to cool naturally in the furnace. After cooling, aluminum nitride copper-clad ceramics are obtained.
[0049] The peel strength of the aluminum nitride copper-clad ceramic prepared according to the comparative example is 11 N / mm.
[0050] Example 1 In this example, the composite brazing filler metal used for brazing aluminum nitride ceramic and oxygen-free copper is composed of the following raw materials and proportions: The silver-copper-titanium filler metal contains 68% silver, 28% copper, and 4% titanium. The niobium powder accounts for 2% of the total mass of the filler metal. The silver-copper-titanium powder has a particle size of less than or equal to 45 μm, while the niobium powder has a particle size of less than or equal to 80 nm.
[0051] The brazing method for brazing a composite brazing material of aluminum nitride ceramic and oxygen-free copper specifically comprises the following steps: Step 1: weigh silver, copper, titanium solder and niobium powder according to the ratio, put them into a ball mill, use alcohol as a dispersion medium, and obtain a uniformly mixed solder suspension after ball milling.
[0052] Step 2: Place the solder suspension in a vacuum drying oven at 50° C. and dry it to obtain a dried composite solder.
[0053] Step 3: Add ethyl cellulose to a mixed solvent formed by terpineol and diethylene glycol butyl ether acetate, heat to 60°C and stir until the ethyl cellulose is completely dissolved to obtain a mixed solution; add hydrogenated castor oil and fatty alcohol polyoxyethylene ether to the obtained mixed solution in sequence, heat to 90°C and stir until completely dissolved, to obtain a solder paste binder with uniform composition.
[0054] The solder paste binder includes: 10wt% of ethyl cellulose, 19wt% of diethylene glycol butyl ether acetate, 3wt% of hydrogenated castor oil, 1wt% of fatty alcohol polyoxyethylene ether and 67wt% of terpineol.
[0055] Step 4: Weigh the composite solder and the solder paste binder in a mass ratio of 9:1 and stir them thoroughly to obtain the composite solder paste.
[0056] Step 5: Coat the bonding area of the aluminum nitride ceramic with composite solder paste, and stack the surface of the aluminum nitride ceramic coated with composite solder paste with oxygen-free copper foil and put it into the furnace. ‒3 The brazing process includes heating to 450°C at a rate of 10°C / min and holding for 30 minutes to volatilize the organic matter in the composite solder paste, and then heating to 880°C and holding for 10 minutes.
[0057] As shown in Table 1, the peel strength of the aluminum nitride copper clad laminate prepared according to Example 1 is 26.1 N / mm. Figure 2 The microstructure of the aluminum nitride ceramic copper clad plate joint. Figure 2 It can be seen that the interface between aluminum nitride ceramic and oxygen-free copper is well bonded and no microcracks are found.
[0058] Example 2 Compared with Example 1, the mass of niobium powder is adjusted in Example 2. For example, the mass of niobium powder is 0wt% of the total mass of the composite solder, that is, no niobium powder is added in Example 2. The specific steps include: Step 1: Weigh silver, copper and titanium solder and put them into a ball milling jar, use alcohol as a dispersion medium, and obtain a solder suspension after ball milling.
[0059] Step 2: Place the solder suspension in a vacuum drying oven at 50° C. and dry it to obtain a dried composite solder.
[0060] Step 3: Add ethyl cellulose to a mixed solvent formed by terpineol and diethylene glycol butyl ether acetate, heat to 60°C and stir until the ethyl cellulose is completely dissolved to obtain a mixed solution; add hydrogenated castor oil and fatty alcohol polyoxyethylene ether to the obtained mixed solution in sequence, heat to 90°C and stir until completely dissolved, to obtain a solder paste binder with uniform composition.
[0061] The solder paste binder includes: 10wt% of ethyl cellulose, 19wt% of diethylene glycol butyl ether acetate, 3wt% of hydrogenated castor oil, 1wt% of fatty alcohol polyoxyethylene ether and 67wt% of terpineol.
[0062] Step 4: Weigh the composite solder and the solder paste binder in a mass ratio of 9:1 and stir them thoroughly to obtain the composite solder paste.
[0063] Step 5: Coat the bonding area of the aluminum nitride ceramic with composite solder paste, and stack the surface of the aluminum nitride ceramic coated with composite solder paste with oxygen-free copper foil and put it into the furnace. ‒3 The brazing process includes heating to 450°C at a rate of 10°C / min and holding for 30 minutes to volatilize the organic matter in the composite solder paste, and then heating to 880°C and holding for 10 minutes.
[0064] As shown in Table 1, the peel strength of the aluminum nitride copper clad laminate prepared according to Example 2 is 15.7 N / mm.
[0065] Example 3 Compared with Example 1, the mass of the niobium powder is adjusted in Example 3. For example, the mass of the niobium powder is 4 wt% of the total mass of the composite solder, that is, the amount of niobium powder added in Example 3 is increased. Specifically, the following steps are included: Step 1: weigh silver, copper, titanium solder and niobium powder according to the ratio, put them into a ball mill, use alcohol as a dispersion medium, and obtain a uniformly mixed solder suspension after ball milling.
[0066] Step 2: Place the solder suspension in a vacuum drying oven at 50° C. and dry it to obtain a dried composite solder.
[0067] Step 3: Add ethyl cellulose to a mixed solvent formed by terpineol and diethylene glycol butyl ether acetate, heat to 60°C and stir until the ethyl cellulose is completely dissolved to obtain a mixed solution; add hydrogenated castor oil and fatty alcohol polyoxyethylene ether to the obtained mixed solution in sequence, heat to 90°C and stir until completely dissolved, to obtain a solder paste binder with uniform composition.
[0068] The solder paste binder includes: 10wt% of ethyl cellulose, 19wt% of diethylene glycol butyl ether acetate, 3wt% of hydrogenated castor oil, 1wt% of fatty alcohol polyoxyethylene ether and 67wt% of terpineol.
[0069] Step 4: Weigh the composite solder and the solder paste binder in a mass ratio of 9:1 and stir them thoroughly to obtain the composite solder paste.
[0070] Step 5: Coat the bonding area of the aluminum nitride ceramic with composite solder paste, and stack the surface of the aluminum nitride ceramic coated with composite solder paste with oxygen-free copper foil and put it into the furnace. ‒3 The brazing process includes heating to 450°C at a rate of 10°C / min and holding for 30 minutes to volatilize the organic matter in the composite solder paste, and then heating to 880°C and holding for 10 minutes.
[0071] As shown in Table 1, the peel strength of the aluminum nitride copper clad laminate obtained according to Example 3 is 25.1 N / mm.
[0072] Example 4 Compared with Example 1, the brazing process parameters in Example 4 are adjusted, specifically the heating rate, the first time, and the second temperature.
[0073] The brazing method for brazing a composite brazing material of aluminum nitride ceramic and oxygen-free copper specifically comprises the following steps: Step 1: weigh silver, copper, titanium solder and niobium powder according to the ratio, put them into a ball mill, use alcohol as a dispersion medium, and obtain a uniformly mixed solder suspension after ball milling.
[0074] Step 2: Place the solder suspension in a vacuum drying oven at 50° C. and dry it to obtain a dried composite solder.
[0075] Step 3: Add ethyl cellulose to a mixed solvent formed by terpineol and diethylene glycol butyl ether acetate, heat to 60°C and stir until the ethyl cellulose is completely dissolved to obtain a mixed solution; add hydrogenated castor oil and fatty alcohol polyoxyethylene ether to the obtained mixed solution in sequence, heat to 90°C and stir until completely dissolved, to obtain a solder paste binder with uniform composition.
[0076] The solder paste binder includes: 10wt% of ethyl cellulose, 19wt% of diethylene glycol butyl ether acetate, 3wt% of hydrogenated castor oil, 1wt% of fatty alcohol polyoxyethylene ether and 67wt% of terpineol.
[0077] Step 4: Weigh the composite solder and the solder paste binder in a mass ratio of 9:1 and stir them thoroughly to obtain the composite solder paste.
[0078] Step 5: Coat the bonding area of the aluminum nitride ceramic with composite solder paste, and stack the surface of the aluminum nitride ceramic coated with composite solder paste with oxygen-free copper foil and put it into the furnace. ‒3 The brazing process includes heating to 450°C at a rate of 3°C / min and holding for 10 minutes to volatilize the organic matter in the composite solder paste, and then heating to 840°C and holding for 10 minutes.
[0079] As shown in Table 1, the peel strength of the aluminum nitride copper clad laminate obtained according to Example 4 is 18.9 N / mm.
[0080] Example 5 Compared with Example 1, Example 5 adjusts the brazing process parameters, specifically the second temperature. Specifically, the process includes the following steps: Step 1: weigh silver, copper, titanium solder and niobium powder according to the ratio, put them into a ball mill, use alcohol as a dispersion medium, and obtain a uniformly mixed solder suspension after ball milling.
[0081] Step 2: Place the solder suspension in a vacuum drying oven at 50° C. and dry it to obtain a dried composite solder.
[0082] Step 3: Add ethyl cellulose to a mixed solvent formed by terpineol and diethylene glycol butyl ether acetate, heat to 60°C and stir until the ethyl cellulose is completely dissolved to obtain a mixed solution; add hydrogenated castor oil and fatty alcohol polyoxyethylene ether to the obtained mixed solution in sequence, heat to 90°C and stir until completely dissolved, to obtain a solder paste binder with uniform composition.
[0083] The solder paste binder includes: 10wt% of ethyl cellulose, 19wt% of diethylene glycol butyl ether acetate, 3wt% of hydrogenated castor oil, 1wt% of fatty alcohol polyoxyethylene ether and 67wt% of terpineol.
[0084] Step 4: Weigh the composite solder and the solder paste binder in a mass ratio of 9:1 and stir them thoroughly to obtain the composite solder paste.
[0085] Step 5: Coat the bonding area of the aluminum nitride ceramic with composite solder paste, and stack the surface of the aluminum nitride ceramic coated with composite solder paste with oxygen-free copper foil and put it into the furnace. ‒3 Brazing is carried out under vacuum conditions of Pa.
[0086] The brazing process in step five includes: first heating to 450° C. at a heating rate of 10° C. / min and holding the temperature for 30 minutes to volatilize organic matter in the composite solder paste, and then heating to 920° C. and holding the temperature for 10 minutes.
[0087] As shown in Table 1, the peel strength of the aluminum nitride copper clad laminate obtained according to Example 5 is 16.5 N / mm.
[0088] Example 6 Compared with Example 1, Example 6 adjusts the brazing process parameters, specifically adjusts the second time, that is, shortens the second time. Specifically, the following steps are included: Step 1: weigh silver, copper, titanium solder and niobium powder according to the ratio, put them into a ball mill, use alcohol as a dispersion medium, and obtain a uniformly mixed solder suspension after ball milling.
[0089] Step 2: Place the solder suspension in a vacuum drying oven at 50° C. and dry it to obtain a dried composite solder.
[0090] Step 3: Add ethyl cellulose to a mixed solvent formed by terpineol and diethylene glycol butyl ether acetate, heat to 60°C and stir until the ethyl cellulose is completely dissolved to obtain a mixed solution; add hydrogenated castor oil and fatty alcohol polyoxyethylene ether to the obtained mixed solution in sequence, heat to 90°C and stir until completely dissolved, to obtain a solder paste binder with uniform composition.
[0091] The solder paste binder includes: 10wt% of ethyl cellulose, 19wt% of diethylene glycol butyl ether acetate, 3wt% of hydrogenated castor oil, 1wt% of fatty alcohol polyoxyethylene ether and 67wt% of terpineol.
[0092] Step 4: Weigh the composite solder and the solder paste binder in a mass ratio of 9:1 and stir them thoroughly to obtain the composite solder paste.
[0093] Step 5: Coat the bonding area of the aluminum nitride ceramic with composite solder paste, and stack the surface of the aluminum nitride ceramic coated with composite solder paste with oxygen-free copper foil and put it into the furnace. ‒3 Brazing is carried out under vacuum conditions of Pa.
[0094] Exemplarily, the brazing process in step five includes: the brazing heat treatment system is: first heating to 450°C at a heating rate of 10°C / min and keeping warm for 30 minutes to volatilize the organic matter in the composite brazing paste, and then heating to 880°C and keeping warm for 5 minutes.
[0095] As shown in Table 1, the peel strength of the aluminum nitride copper clad laminate obtained according to Example 6 is 23.6 N / mm.
[0096] Example 7 Compared with Example 1, Example 7 adjusts the brazing process parameters, specifically adjusting the second time, that is, increasing the second time. Specifically, the following steps are included: Step 1: weigh silver, copper, titanium solder and niobium powder according to the ratio, put them into a ball mill, use alcohol as a dispersion medium, and obtain a uniformly mixed solder suspension after ball milling.
[0097] Step 2: Place the solder suspension in a vacuum drying oven at 50° C. and dry it to obtain a dried composite solder.
[0098] Step 3: Add ethyl cellulose to a mixed solvent formed by terpineol and diethylene glycol butyl ether acetate, heat to 60°C and stir until the ethyl cellulose is completely dissolved to obtain a mixed solution; add hydrogenated castor oil and fatty alcohol polyoxyethylene ether to the obtained mixed solution in sequence, heat to 90°C and stir until completely dissolved, to obtain a solder paste binder with uniform composition.
[0099] The solder paste binder includes: 10wt% of ethyl cellulose, 19wt% of diethylene glycol butyl ether acetate, 3wt% of hydrogenated castor oil, 1wt% of fatty alcohol polyoxyethylene ether and 67wt% of terpineol.
[0100] Step 4: Weigh the composite solder and the solder paste binder in a mass ratio of 9:1 and stir them thoroughly to obtain the composite solder paste.
[0101] Step 5: Coat the bonding area of the aluminum nitride ceramic with composite solder paste, and stack the surface of the aluminum nitride ceramic coated with composite solder paste with oxygen-free copper foil and put it into the furnace. ‒3 Brazing is carried out under vacuum conditions of Pa.
[0102] Exemplarily, the brazing process in step five includes: the brazing heat treatment system is: first heating to 450°C at a heating rate of 10°C / min and keeping warm for 30 minutes to volatilize the organic matter in the composite brazing paste, and then heating to 880°C and keeping warm for 30 minutes.
[0103] As shown in Table 1, the peel strength of the aluminum nitride copper clad laminate obtained according to Example 7 is 20.4 N / mm.
[0104] Table 1
[0105] In summary, when the niobium powder addition amount is 2wt%, the first brazing temperature is 880°C, and the first holding time is 10 minutes, the peel strength of the aluminum nitride and oxygen-free copper joint reaches a maximum of 26.1N / mm. This peel strength is 1.7 times that of the brazed joint without niobium powder. The peel strength of the aluminum nitride ceramic and oxygen-free copper joint obtained in the disclosed embodiments is far superior to the peel strength reported in the related art.
[0106] In the disclosed embodiments, the addition of niobium particles reduces the thermal expansion coefficient of the solder alloy, and the niobium particles can undergo a certain degree of plastic deformation during the load-bearing process to absorb some energy, thereby solving the problems of large residual stress and low joint strength in the joints between aluminum nitride ceramics and oxygen-free copper in the related art, and achieving high-quality welding of aluminum nitride ceramics and oxygen-free copper.
[0107] In addition, embodiments of the present disclosure also provide a composite brazing filler metal for use in brazing aluminum nitride ceramics to oxygen-free copper. The composite brazing filler metal includes a silver-copper-titanium brazing filler metal and niobium powder. The silver-copper-titanium brazing filler metal comprises 68.0-70.5 wt% silver, 4.0-5.0 wt% titanium, and copper. The mass of the niobium powder accounts for 0-10 wt% of the total mass of the composite brazing filler metal.
[0108] Niobium particles are used to reinforce silver-copper-titanium composite brazing filler metals to join aluminum nitride ceramics and oxygen-free copper. By adding niobium particles to the silver-copper-titanium brazing filler metal, the thermal expansion coefficient of niobium is significantly lower than that of the silver-copper-titanium brazing filler metal, thereby reducing the thermal expansion coefficient mismatch between the aluminum nitride ceramics and oxygen-free copper. This reduces joint stress, improves joint strength, and achieves high-quality welding between the aluminum nitride ceramics and oxygen-free copper. Furthermore, due to niobium's good ductility, the niobium particles can undergo a certain degree of plastic deformation during load-bearing, absorbing some of the energy, alleviating stress concentration within the brazing filler metal layer and improving the welding effect.
[0109] Furthermore, the figures above are merely illustrative of the processes included in the methods according to exemplary embodiments of the present disclosure and are not intended to be limiting. It is readily understood that the processes illustrated in the figures above do not indicate or limit the temporal order of these processes. Furthermore, it is readily understood that these processes may be executed synchronously or asynchronously, for example, in multiple modules.
[0110] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary techniques in the art not disclosed herein. The description and examples are to be considered as exemplary only, with the true scope and spirit of the present disclosure being indicated by the appended claims.
[0111] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes can be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A brazing method for aluminum nitride ceramics and oxygen-free copper, characterized in that: include: Silver-copper-titanium solder and niobium powder are placed in a ball mill and ball milled with alcohol as a dispersion medium to obtain a solder suspension. drying the solder suspension to obtain a dried composite solder; Ethyl cellulose is added to a mixed solvent of terpineol and diethylene glycol butyl ether acetate, and the mixture is heated and dissolved to obtain a mixed solution. Hydrogenated castor oil and fatty alcohol polyoxyethylene ether are sequentially added to the mixed solution, and the mixture is heated until dissolved to obtain a solder paste binder with uniform composition. Stirring the composite solder and the solder paste binder to obtain the composite solder paste; The bonding area of the aluminum nitride ceramic is coated with a composite solder paste, and an oxygen-free copper foil is stacked on the aluminum nitride ceramic coated with the composite solder paste for brazing.
2. The brazing method of aluminum nitride ceramic and oxygen-free copper according to claim 1, characterized in that: The composite solder includes silver-copper-titanium solder and niobium powder. The silver-copper-titanium solder contains 68.0-70.5wt% silver, 4.0-5.0wt% titanium and copper. The mass of the niobium powder is 0-10wt% of the total mass of the composite solder.
3. The brazing method of aluminum nitride ceramic and oxygen-free copper according to claim 1, characterized in that: The method of drying the solder suspension to obtain a dried composite solder comprises: The solder suspension is placed in a vacuum drying oven and dried at a target temperature to obtain a dried composite solder; the target temperature is less than or equal to 80°C.
4. The brazing method of aluminum nitride ceramic and oxygen-free copper according to claim 1, characterized in that: The particle size of the silver-copper-titanium powder is less than or equal to 45 μm, and the particle size of the niobium powder is less than or equal to 80 nm.
5. The brazing method of aluminum nitride ceramic and oxygen-free copper according to claim 1, characterized in that: The solder paste adhesive comprises: 5-15 wt% ethyl cellulose, 15-25 wt% diethylene glycol butyl ether acetate, 1-5 wt% hydrogenated castor oil, 0.1-3 wt% fatty alcohol polyoxyethylene ether and terpineol.
6. The brazing method of aluminum nitride ceramic and oxygen-free copper according to claim 1, characterized in that: The mass ratio of the composite solder to the solder paste binder is 9:1 to 8:
2.
7. The brazing method of aluminum nitride ceramic and oxygen-free copper according to claim 1, characterized in that: The method of stacking oxygen-free copper foil on aluminum nitride ceramic coated with composite brazing material for brazing comprises: The aluminum nitride ceramic coated with composite solder is stacked with oxygen-free copper foil and placed in a furnace. The temperature is raised to a first temperature and kept for a first time at a heating rate under a target vacuum degree, and then raised to a second temperature and kept for a second time to braze the aluminum nitride ceramic and the oxygen-free copper foil.
8. The brazing method of aluminum nitride ceramic and oxygen-free copper according to claim 7, characterized in that: The target vacuum degree is higher than 3×10 ‒3 Pa.
9. The brazing method of aluminum nitride ceramic and oxygen-free copper according to claim 7, characterized in that: The heating rate is 3°C / min to 10°C / min, the first temperature is 450°C, the first time is 10min to 30min, the second temperature is 840°C to 920°C, and the second time is 5min to 20min.
10. A composite solder, characterized in that: The composite brazing filler metal is used to perform the brazing method of aluminum nitride ceramic and oxygen-free copper according to any one of claims 1 to 9; The composite solder includes silver-copper-titanium solder and niobium powder, wherein the silver-copper-titanium solder includes 68.0-70.5wt% silver, 4.0-5.0wt% titanium and copper, and the mass of the niobium powder is 0-10wt% of the total mass of the composite solder.
Citation Information
Patent Citations
Si3N4 and 42CrMo steel connecting solder and brazing connection method
CN102699574A
Solder, preparation method thereof and method for connecting sapphire and niobium or niobium alloys by using solder
CN103056553A
Method for relieving residual stress of brazed joint
CN103143805A
Tungsten / copper joint with copper-based brazing filler metal added with copper foil and preparing method thereof
CN108746910A
Brazing filler metal for connecting high Nb-TiAl alloy with aluminum oxide ceramics and connecting method thereof
CN110369907A